2019
DOI: 10.18632/aging.102465
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 27b promotes cardiac fibrosis by targeting the FBW7/Snail pathway

Abstract: Our study aspires to understand the impact of miR-27b on myocardial fibrosis as well as its functional mechanism. 12 days post the ligation of coronary artery in rats, the expression of miR-27b in the peri-infarction region was elevated. Treating cultivated rat neonatal cardiac fibroblasts (CFs) with angiotensin II (AngII) also enhanced the miR-27b expression. Forced expression of miR-27b promoted the proliferation and collagen production in rat neonatal CFs, as revealed by cell counting, MTT assay, and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Primary CFs were isolated from neonatal mice (1–2-day-old) using a previously described method. 24 Briefly, neonatal mice were quickly rinsed in 75% ethanol and decapitated. The heart was removed, atrium was excised, and the ventricles were minced and washed with PBS at 4°C to remove excess blood.…”
Section: Methodsmentioning
confidence: 99%
“…Primary CFs were isolated from neonatal mice (1–2-day-old) using a previously described method. 24 Briefly, neonatal mice were quickly rinsed in 75% ethanol and decapitated. The heart was removed, atrium was excised, and the ventricles were minced and washed with PBS at 4°C to remove excess blood.…”
Section: Methodsmentioning
confidence: 99%
“…siRNA mediated inhibition of MMP-9 significantly reduces expression of Snail, and conversely, knockdown of Snail, a transcription factor of MMP-9, suppresses expression of MMP-9 (39). FBW7 abrogation of Snail protein also inhibits MMP-9 expression (40). Interestingly, MCV sT induced Snail expression in our initial transcriptional analysis (Fig.…”
Section: St Activates Expression Of Emt Regulator Snailmentioning
confidence: 67%
“…In this report, we show that MCV sT LSD inhibition of FBW7 promotes the upregulation of MMP-9 and contributes to MCV sT-mediated cell migration and invasion. The mechanism by which FBW7 regulates MMP-9 expression is currently unclear, although many studies have shown MMP-9 expression is directly and indirectly regulated by FBW7 substrates such as XBP1, Notch1, and Snail (12,40,51). Snail is known to be a substrate of both FBW7 (40) and -TrCP (52), another major SCF E3 ligase that MCV sT targets through the LSD (7).…”
Section: Discussionmentioning
confidence: 99%
“…The sections were stained according to the HE staining procedure. After sealing with a neutral resin (Solarbiolife sciences, G8590), the slices were photographed using an optical microscope (Leica Microsystems, DMILLED) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%